2021
DOI: 10.1111/ajgw.12535
|View full text |Cite
|
Sign up to set email alerts
|

Whole bunch fermentation and the use of grape stems: effect on phenolic and volatile aroma composition ofVitis viniferacv. Pinot Noir wine

Abstract: Background and Aims Whole bunch fermentation is widely used in red wine production but research on whole bunch fermentation is limited, especially for cool climate Pinot Noir. Inclusion of whole bunches or grape stems was investigated in Pinot Noir wine production with respect to extraction of phenolic compounds and aroma production. Methods and Results Five Pinot Noir wines were microvinified by including grape stems or whole bunches at various levels: destemmed grapes (DS), 100% stems added back (DS100), 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 57 publications
6
18
0
Order By: Relevance
“…MPs are varietal aroma impact compounds for many Bordeaux varieties, including Cabernet Sauvignon and Sauvignon blanc, contributing “green capsicum”, “leafy”, and “grassy” aromas at concentrations as low as 10 to 15 ng/L. , At concentrations exceeding 15 ng/L in red wine, MPs may impart an overpowering “green bell pepper” aroma, decreasing perceptions of desirable fruity and floral aromas . While the presence of MPs in rachis and berry of Cabernet Sauvignon , and other cultivars ,, is well established, the impact of rootstocks on MP concentrations in wine was unknown until recently. A study in 2022 showed that Ramsey (Vitis candicans × Vitis rupestris), the most common rootstock in South Australia, can increase the concentration of MPs in the rachis of Shiraz approximately eight times above the concentration in rachis from vines grown on own roots .…”
Section: Introductionmentioning
confidence: 99%
“…MPs are varietal aroma impact compounds for many Bordeaux varieties, including Cabernet Sauvignon and Sauvignon blanc, contributing “green capsicum”, “leafy”, and “grassy” aromas at concentrations as low as 10 to 15 ng/L. , At concentrations exceeding 15 ng/L in red wine, MPs may impart an overpowering “green bell pepper” aroma, decreasing perceptions of desirable fruity and floral aromas . While the presence of MPs in rachis and berry of Cabernet Sauvignon , and other cultivars ,, is well established, the impact of rootstocks on MP concentrations in wine was unknown until recently. A study in 2022 showed that Ramsey (Vitis candicans × Vitis rupestris), the most common rootstock in South Australia, can increase the concentration of MPs in the rachis of Shiraz approximately eight times above the concentration in rachis from vines grown on own roots .…”
Section: Introductionmentioning
confidence: 99%
“…Pinot noir wine was made using standard method in our lab (Wimalasiri et al., 2022). In brief, all winemaking treatments underwent a 5 day cold soaking before the inoculation of EC1118 yeast (Lallemand, Montréal, QC, Canada), followed by 4 days of post‐fermentation maceration.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study (Wimalasiri et al, 2022) showed that the inclusion of whole bunches or grape stems during fermentation had a great impact on aroma profile of Pinot noir wine at the end of alcoholic fermentation. This study focuses on wine colour, aiming to evaluate the short-term and long-term influence of whole bunches or grape stems addition on the colour development in Pinot noir wine.…”
Section: Introductionmentioning
confidence: 97%
“…Winemakers may opt to include rachis during whole-or partial-bunch fermentation to produce desirable tannin [9,10], colour [10,11], pH, or ethanol changes to the wine [9,12]. However, these techniques are avoided for varieties that are known to produce IBMP (an impact odorant with green capsicum character) in rachis and berry, such as Cabernet Sauvignon, because they can cause the perception of "stemmy" favours in wine [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques are avoided for varieties that are known to produce IBMP (an impact odorant with green capsicum character) in rachis and berry, such as Cabernet Sauvignon, because they can cause the perception of "stemmy" favours in wine [13]. Even for varieties where a portion of whole bunches is favourable in producing quality wines, such as Pinot noir, stem addition exceeding 60% can produce wines with sensory characteristics associated with MPs [9]. Rachis can also be unintentionally present during fermentation as a by-product of harvesting and destemming practices, as a component of matter other than grape (MOG).…”
Section: Introductionmentioning
confidence: 99%